TUAN GURU HAJI KASYFUL ANWAR DAN KIPRAHNYA DI PONDOK PESANTREN DARUSSALAM MARTAPURA - Mubarak, Ahmad Taufik (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
This paper explores the role of Tuan Guru Haji Kasyful Anwar in making some changes in Pondok Pesantren Darussalam Martapura. The changing that he made in that Islamic boarding school can be seen in system of teaching, curriculum, and the facilities of study. Also in his period found the degree of education. He taught his students to have a humble life besides to apply the knowledge as maximal as possible. So that, from his boarding school and his public class that belong to him, came out many ulama.